The EPA Cancer Risk Assessment Default Model Proposal: Moving Away From the LNT - Edward J. Calabrese; Jaap C. Hanekamp; Dima Yazji Shamoun (SAGE Publishing, 2018)
This article strongly supports the Environmental Protection Agency proposal to make significant changes in their cancer risk assessment principles and practices by moving away from the use of the linear nonthreshold (LNT) dose-response as the default model. An alternate approach is proposed based on model uncertainty which integrates the most scientifically supportable features of the threshold, hormesis, and LNT models to identify the doses that optimize population-based responses (ie, maximize health benefits/minimize health harm). This novel approach for cancer risk assessment represents a significant improvement to the current LNT default method from scientific and public health perspectives.